Strategi Pemasaran Online Melalui Tik Tok Shop pada Hasil Penjualan Kripik Pisang di Desa Sri Tanjung Kecamatan Semendwai Barat Kabupaten Oku Timur - Leo Mursid; Kuatno Kuatno; Mursilah Mursilah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Indonesia is widely known as an agricultural country, with the majority of its population depending on this sector for their livelihood. Agriculture plays an important role in driving national economic development, making a significant contribution to the structure of the Indonesian economy. This not only provides the majority of employment opportunities but also functions as the main source of state income through its impact on Gross Domestic Product (GDP). Apart from the agricultural sector, there is also a production sector that encourages a country's income to increase, whether in small, medium or large production. big. The development of the industrial world in Indonesia is increasingly developing, especially in the snack food industry which is highly sought after by consumers in a region. With the development of the digital world, the marketing process for snacks is becoming more widespread. Tik Tok media is one of the social media that is increasingly trending and is loved by all levels of society from children to old age. This is where snack producers use TikTok social media.